2000
DOI: 10.1128/mcb.20.16.6084-6094.2000
|View full text |Cite
|
Sign up to set email alerts
|

A Lipopolysaccharide-Specific Enhancer Complex Involving Ets, Elk-1, Sp1, and CREB Binding Protein and p300 Is Recruited to the Tumor Necrosis Factor Alpha Promoter In Vivo

Abstract: The tumor necrosis factor alpha (TNF-␣) gene is rapidly activated by lipopolysaccharide (LPS). Here, we show that extracellular signal-regulated kinase (ERK) kinase activity but not calcineurin phosphatase activity is required for LPS-stimulated TNF-␣ gene expression. In LPS-stimulated macrophages, the ERK substrates Ets and Elk-1 bind to the TNF-␣ promoter in vivo. Strikingly, Ets and Elk-1 bind to two TNF-␣ nuclear factor of activated T cells (NFAT)-binding sites, which are required for calcineurin and NFAT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
253
2
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 242 publications
(279 citation statements)
references
References 58 publications
22
253
2
2
Order By: Relevance
“…Furthermore, we were unable to detect a DH site in intron 3 in LPS-or mock-stimulated murine monocytic J774 cells (R. Barthel and A. E. Goldfeld, unpublished). Here we also show cell type-specific DH sites in the proximal promoter, in sequences between the TSS and the ATG, and in the 3ЈUTR, regions that have previously been shown to play important functional roles in TNF-␣ gene regulation (1,3,4,9,11,12). Consistent with our findings, we note that constitutive DH sites have been identified in the IL-2 gene that are cell lineage specific and that distinguish IL-2 producer and nonproducer T cells (13).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Furthermore, we were unable to detect a DH site in intron 3 in LPS-or mock-stimulated murine monocytic J774 cells (R. Barthel and A. E. Goldfeld, unpublished). Here we also show cell type-specific DH sites in the proximal promoter, in sequences between the TSS and the ATG, and in the 3ЈUTR, regions that have previously been shown to play important functional roles in TNF-␣ gene regulation (1,3,4,9,11,12). Consistent with our findings, we note that constitutive DH sites have been identified in the IL-2 gene that are cell lineage specific and that distinguish IL-2 producer and nonproducer T cells (13).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have demonstrated the important functional roles of the proximal promoter, the region from the TSS to the ATG and the 3ЈUTR in TNF-␣ gene regulation (3,4,9). To test whether intron 3 might also contain a regulatory element, we examined the effect of the addition of intron 3 on the regulation of a TNF-␣ luciferase reporter gene.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are consistent with the idea that the CREB binding site (Ϫ1267 to Ϫ1260) plays a role in the LPS-mediated mTLR2 induction. It has recently been reported that CREB plays a role in the TNF-␣ mRNA induction by LPS in macrophages (28). In another report, it has been revealed that CREB is activated by LPS through p38 stress-activated protein kinase and is involved in the up-regulation of CD80, CD83, and CD86 (31).…”
Section: Discussionmentioning
confidence: 99%